Altered Jagged1-Notch1 Signaling in Enhanced Dysfunctional Neovascularization and Delayed Angiogenesis After Ischemic Stroke in HFD/STZ Induced Type 2 Diabetes Rats - Guo, Zhihui; Jia, Jia; Tu, Yanling; Jin, Chang; Guo, Cen; Song, Feifei; Wu, Xuqing; Bao, Haifeng; Fan, Wei (Frontiers in Physiology, 2021)
Pre-existing diabetes mellitus worsens brain functionality in ischemic stroke. We have previously shown that type 2 diabetic rats exhibit greater neurological deficits and increased volume of cerebral infarction and brain edema as well as the blood brain barrier permeability after cerebral ischemia. However, our knowledge of the mechanisms of how diabetes impacts the cerebrovascular repair process is limited. This study was aimed to characterize structural alterations and potential mechanisms in cerebral microvasculature before and after experimental cerebral ischemia in the high-fat diet-fed, streptozotocin (HFD/STZ)-treated rat model of type 2 diabetes. We furtherly tested the hypothesis that dysregulated intercellular Jagged1-Notch1 signaling was involved in the dysfunctional cerebral neovascularization both before and after focal cerebral ischemia in the HFD/STZ rats. In our study, we found increased yet dysfunctional neovascularization with activated Jagged1-Notch1 signaling in the cerebrovasculature of HFD/STZ rats before cerebral ischemia. Furthermore, we observed delayed angiogenesis as well as suppressed Jagged1-Notch1 signaling after permanent middle cerebral artery occlusion in HFD/STZ rats compared with nondiabetic rats. Our results shed new light on the potential mechanisms underlying diabetes-related cerebral microvasculature dysfunction after ischemic stroke.